Research on the construction of an urban underground parking space color system from the perspective of psychological perception. - Yuan Lv; Yanjun Shen; Boyuan Li; Jincheng Huang; Hou'an Luo (PLoS ONE)
Color, an intuitive element affecting human senses, can adapt to the environment of a space, evoke emotional responses, trigger and accumulate visual experiences, and enhance the effectiveness of color in shaping spatial atmosphere and reinforcing spatial divisions. In the context of rapid urban underground space development, examining the rational application of color in underground parking spaces is crucial for improving guidance, comfort, and aesthetics. This exploration is essential for achieving high-quality development in urban underground parking environments. Based on color psychology and using typical cities in China as case studies, this paper develops a color analytical framework for urban underground parking spaces through the process of "color field investigation-analysis of color influencing factors-color system construction-color application and control" and proposes a detailed chromatographic scheme. Within this framework, color field investigation serves as the foundation for determining color usage. Key influencing factors for color selection include color elements and their relationships, the type of underground parking space, and public color perception demands. The color system has been constructed including safe colors, prohibited colors, and theme colors, which has been further divided into basic, auxiliary, and accent colors. This study provides a replicable and practical theoretical and applied framework for urban underground space management and urban color planning. The framework facilitates the establishment of a standardized color system and chromatographic scheme that aligns with urban aesthetics and public psychology, thereby improving development quality and supporting the high-quality development of urban underground spaces.